2019
DOI: 10.7554/elife.47678
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-regulated transcription of ESRP2 drives alternative splicing patterns in prostate cancer

Abstract: Prostate is the most frequent cancer in men. Prostate cancer progression is driven by androgen steroid hormones, and delayed by androgen deprivation therapy (ADT). Androgens control transcription by stimulating androgen receptor (AR) activity, yet also control pre-mRNA splicing through less clear mechanisms. Here we find androgens regulate splicing through AR-mediated transcriptional control of the epithelial-specific splicing regulator ESRP2. Both ESRP2 and its close paralog ESRP1 are highly expressed in prim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 80 publications
(118 reference statements)
7
60
0
Order By: Relevance
“…This suggests that pharmacological manipulation of AR may alter splicing by regulating expression and binding of ESRP1/2 around spliced exons. Consistent with our findings, Munkley et al, recently published their findings suggesting that androgen stimulation induces splicing switches in ESRP2-controlled mRNA isoforms [43]. We also inquired whether AR-axis may regulate splicing by a nontranscriptional mechanism.…”
Section: Direct Genomic Inhibition Of Ar In Prostate Cancer Cells Indsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that pharmacological manipulation of AR may alter splicing by regulating expression and binding of ESRP1/2 around spliced exons. Consistent with our findings, Munkley et al, recently published their findings suggesting that androgen stimulation induces splicing switches in ESRP2-controlled mRNA isoforms [43]. We also inquired whether AR-axis may regulate splicing by a nontranscriptional mechanism.…”
Section: Direct Genomic Inhibition Of Ar In Prostate Cancer Cells Indsupporting
confidence: 90%
“…Munkley et al recently used the genomic knockdown of ESRPs to identify global splicing changes associated with ESRPs in prostate cancer cells. They also found that a subset of ESRP1/2 regulated exons were also regulated by androgen treatment [43]. However, the study did not address whether or not AR-axis induces global splicing changes in prostate cancer cells beyond those regulated by ESRPs.…”
Section: Discussionmentioning
confidence: 90%
“…We have shown that ESRP1, though an ESRP2 paralogue, is not hypermethylated in WTs ( figure 2B, C), suggesting that ESRP1 and ESRP2 may have different biological functions and are regulated differently in some instances. Similarly, a recent paper (68) has reported that only ESRP2 and not ESRP1 is regulated by androgens, with important implications in prostate cancer progression.…”
Section: Discussionmentioning
confidence: 82%
“…Establishing the network between OS-related AS events and tumor-specific SFs, this research found that ESRP1 was associated with several OS-AS events that were correlated with OS. Similarly, ESRP1 was considered avital SF that leads to the progression and metastasis in pancreatic and prostate cancer [53,54]. While in addition to its role in splicing, PTBP1 also participates in the regulation of other aspects of RNA metabolism.…”
Section: Discussionmentioning
confidence: 99%